2014
DOI: 10.3109/09638288.2014.961655
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for discharge destination after acute stroke: a comprehensive literature review

Abstract: Patient initial medical care, age and sex, neurological and medical complications and environmental/socio-economic factors should be considered in the decision-making process for discharge destination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 42 publications
2
28
5
Order By: Relevance
“…Although we used a modified version of the Charlson Comorbidity Index specifically for predicting stroke outcomes, previous studies indicated that there was an association between comorbidity and discharge destination. 38 In addition, it is known that preexisting comorbidities are negatively associated with functional rehabilitation outcomes in stroke patients. 39 Another study reported that the mCCI on admission was an independent indicator of unfavorable functional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Although we used a modified version of the Charlson Comorbidity Index specifically for predicting stroke outcomes, previous studies indicated that there was an association between comorbidity and discharge destination. 38 In addition, it is known that preexisting comorbidities are negatively associated with functional rehabilitation outcomes in stroke patients. 39 Another study reported that the mCCI on admission was an independent indicator of unfavorable functional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…From the literature it becomes clear that discharge destination is related to post-admission functional ability, age, cognitive abilities, and availability of social support (4)(5)(6). A systematic review showed that older patients with more comorbidities are more likely to be discharged to inpatient rehabilitation or long-term care after an acute stroke, rather than being discharged home (7). Another systematic review on prognostic indicators of acute hospital discharge disposition after stroke included 48 cohort studies with, in general, poor methodological quality (8).…”
Section: Introductionmentioning
confidence: 99%
“…Discharge destination after acute stroke has been reported to be predicted by many factors, including age, race, gender, medical complications/comorbidities, neurological complications, and environmental and socioeconomic factors [4]. In particular, younger age has been identified as a significant factor for being discharged home [7−9].…”
mentioning
confidence: 99%